PELAPORAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI PADA KEGIATAN RELAWAN PAJAK - Fiqih, Muhammad; Widjaja, Djeni Indrajati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Every year, especially during the individual taxpayer reporting period which ends on March 31 of the following period, tax service office employees are very busy. On the one hand, taxpayers already have the awareness to fulfill their tax obligations, namely reporting their annual tax return, but many taxpayers face reporting problems so they need help filling out individual taxpayers' annual tax returns. This community service event is part of the Tarumanagara University Tax Center. This tax volunteer team process is carried out after receiving messages from partners regarding assistance for accompanying taxpayers in filling out tax returns and participation in tax education programs and methods for implementing tax volunteer teams through several steps, starting from the recruitment stage, determining the tax volunteer team, providing guidance. taxation for the tax Volunteer Team. Implementation of assistants for filling out WPOP Annual SPT at KPP Pratama Jakarta Tambora. Activities of the WPOP accompanying tax volunteer team in reporting Annual SPT and matching NIK to NPWP directly at KPP Pratama Jakarta Tambora. This activity starts on 01 March 2023 and ends on 31 March 2023, with services from 09:00 to 16:00 WIB. From the results of WPOPs who filled out questionnaires of more than 15 WPOPs, the evaluation results were very satisfying for the tax volunteer team in terms of knowledge, ethics and communication, especially in tax volunteer assistance activities to taxpayers, besides that the Tax volunteer team is a form of integrating tax awareness, increasing Taxpayer compliance. The Jakarta Tambora Primary Tax Service Office through the West Jakarta Tax Directorate General collaborates with the Tarumanagara University Tax Center. Types of collaboration as tax volunteers include assisting taxpayers, filling out tax forms, and participating in tax education programs. From the results of this evaluation, it can be recommended that this activity continue in the next period.